Supernumerary impacted teeth in the mental nerve region: case report (Research, Society and Development, 2021)
Introduction: During tooth development, disorders can affect the developing germ, causing changes in number, shape, size, position and structure. The occurrence of supernumerary teeth represents an abnormality that is more prevalent in permanent dentition.  This occurrence, when related to the premolar region, differs from the others, having a higher frequency, and this fact can be explained by the fact that they are one of the last teeth to erupt in the dental arch. A good clinical examination, associated with the request of complementary exams are fundamental for an early and promising diagnosis. Imaging exams become indispensable to determine the location of the extranumerary element, besides visualizing possible proximities with adjacent noble structures. Objective: To report a clinical case of extraction of supernumerary and impacted teeth for orthodontic purposes, and to highlight the importance of a detailed anamnesis. Case Report: A patient sought the services of a private dental clinic with an orthodontic indication for removal of supernumerary teeth. The treatment indicated to the patient was the exodontia of the supernumerary elements so that the orthodontic movement could occur in a correct manner. Conclusion: The removal of hyperdontic elements in the vast majority of cases is essential in order to avoid further harm to the patient. For this procedure to be safely performed, a detailed clinical examination should always be carried out, combined with a request for complementary imaging tests, in order to better evaluate the structures adjacent to the anomalous element.